Penerapan PENERAPAN METODE STRUKTURAL ANALITIK SINTETIK BERBANTUAN MEDIA GAMBAR SEBAGAI UPAYA MENINGKATKAN KETERAMPILAN MEMBACA PERMULAAN SISWA SEKOLAH DASAR - Yunsacitra; Ahmad Hariandi; Muhammad Sholeh (Jurnal Tunas Pendidikan, 2025)
This research aims to describe the improvement of beginning reading skills through the application of the Synthetic Analytical Structural (SAS) method in grade 1 elementary school students. This research wa carried out at SDN 207/IV Jerambah Bolong, South Jambi sub-district, Jambi city, Jambi province. The form of this research is Classroom Action Research (CAR) using a qualitative approach. This research data was obtained by observation. Interviews, documentation, and tests. This research was carried out in 2 meetings. Each cycle consistsof four stages, namely planning, implementation, observation, and reflection. The results of this reserach were that there was an increase in intial reading skills in grade 1 students at SDN 207/IV Jerambah Bolong after applying the Synthetic Analytical Structural (SAS) method at each meeting in each cycle.